Microbiological safety of Thai pandan custard filled products and their ingredients - Puangburee, S.; Jindaprasert, A.; Vattanmanee, S.; Wongsommart, D.; Swetwiwathana, A. (My University, 2016)
The aim of this study was to evaluate microbiological quality of Thai pandan custard and their main ingredients used in the product such as pandan leaves, whole egg, pasteurized coconut milk, cornstarch, wheat flour and sugar. The ingredients and Thai pandan custard were collected from some small and medium enterprises in the center of Thailand by sampling 20 samples of high risk ingredients (pandan leaves, whole egg, pasteurized coconut milk), 10 samples of low risk ingredients (cornstarch, wheat flour, sugar) and 20 samples of Thai pandan custard. The samples were tested for four pathogens including Staphylococcus aureus, Salmonella spp., Bacillus cereus and Clostridium perfringens. It was found that B. cereus was mostly detected in pandan leaves. This pathogenic microorganism was found to contaminate 80% of the leaves (16 samples) with higher than 3 log CFU/g and 15% (3 samples) with lower than 3 log CFU/g. Besides, S. aureus was detected in two samples (10% of the leave sample). Salmonella spp. was shown positive in four samples (20% of whole egg samples), while C. perfringens was not detected in any samples. Moreover, B. cereus was detected in five samples (25%) of the sampling Thai pandan custard after one-day storage at room temperature and the contamination was raised up to 9 samples (45%) after two-day storage with the microbial load of 2.4 to 3.9 log CFU/g. Salmonella spp. and S. aureus were not detected in any sample. The identification of some isolates of B. cereus selected from Thai pandan custard samples by Bureau of Quality and Safety of Food (BQSF), Department of Medical Sciences (DMSc) confirmed that all selected spore-forming bacterial colonies were identified as pathogenic B. cereus. The results from this study implied that heating process during Thai pandan custard production was not effective for diminishment of the contaminated B. cereus from ingredients which might lead to the safety problem of the product.
Keywords: Bacillus cereus; Microbiological safety; Pandan leaf; Thai Pandan Custard